Strategic assessment of fintech platforms in using fuzzy LMAW and fuzzy CRADIS methods - Dervishaj, Blerina; Peci, Arianit; Puška, Adis; Štilić, Anđelka; Pamučar, Dragan; Božanić, Darko (Edelweiss Applied Science and Technology, 2025)
In a rapidly growing market like the Albanian one, FinTech platforms are playing an increasingly important role in transforming how financial transactions are conducted. The research aims to perform a strategic assessment of ten FinTech platforms currently operating in Albania based on 12 strategic criteria. The assessment is based on multi-criteria decision-making methods (MCDM). For this, a model based on the fuzzy approach was developed, allowing for the management of uncertainty and subjectivity in evaluating the performance and suitability of the platforms. Specifically, the fuzzy LMAW method was used to weight the criteria, with Security being assigned the highest weight. The ranking of the platforms was conducted using the fuzzy CRADIS method, with EasyPay achieving the best results. Through this model, the research seeks to provide an objective ranking of the platforms based on each criterion’s relative contribution. The findings are expected to help developers, investors, and policymakers better understand the competitive positioning of current players. The results may also highlight areas for further improvement and growth in Albania's FinTech sector.